2015
DOI: 10.1097/wnp.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Auditory and Somatosensory Evoked Potentials in Relation to Clinical and Neuroimaging Findings in Chiari Type 1 Malformation

Abstract: A high percentage of patients with CM-1 show EP alterations regardless of their clinical or radiological findings, thus highlighting the necessity of performing these tests, especially in patients with few or no symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…BAEPs were abnormal in 77 patients (38.5%). Excluding our preliminary report published elsewhere, 31 to our knowledge, only 1 other study with more than 20 patients has described the findings of BAEPs in patients with classic CM-1. 17 Henriques Filho and Pratesi reported that the most frequent abnormality found in BAEPs in classic CM-1 was on a cochlear or auditory peripheral level.…”
Section: Ep Findingsmentioning
confidence: 87%
See 2 more Smart Citations
“…BAEPs were abnormal in 77 patients (38.5%). Excluding our preliminary report published elsewhere, 31 to our knowledge, only 1 other study with more than 20 patients has described the findings of BAEPs in patients with classic CM-1. 17 Henriques Filho and Pratesi reported that the most frequent abnormality found in BAEPs in classic CM-1 was on a cochlear or auditory peripheral level.…”
Section: Ep Findingsmentioning
confidence: 87%
“…Methods described below have been described in detail elsewhere. 31 In summary, BAEPs and SSEPs in patients with CM-1 were recorded using a Nicolet Viking-IV EMG/EP unit (Nicolet) following the guidelines of the American Electroencephalographic Society, 1 the "Recommendations for the clinical use of somatosensory-evoked potentials," 14 and the "IFCN recommended standards for short latency somatosensory evoked potentials." 34 To obtain normative data, we used a second device, the Viking Select (Viasys Healthcare), acquired in 2010.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between intraspinal abnormality and neurophysiological monitoring has been documented in the literature 8 , 11 , 12 , 17 . Morioka et al .…”
Section: Discussionmentioning
confidence: 93%
“…While we agree with Dr. Adelson that the literature contains plenty of case reports, to our knowledge, only a few studies-all with very limited and heterogeneous series of patients-have described the findings of BAEPs and SSEPs in CM. With the exception of our preliminary article published elsewhere, 9 most studies (noted in our paper) included fewer than 28 patients. Based on the analysis of a large cohort, we aimed to answer some of the questions regarding the role of EPs in the diagnosis of the CM and their relationship with both the clinical findings and the severity of the malformation.…”
Section: The Reliability Of Eps and Their Clinical Usefulnessmentioning
confidence: 89%